Pemodelan Markov Switching Autoregressive untuk Peramalan Data Tingkat Inflasi di Provinsi Jawa Barat Tahun 2009-2022 - Choerunnisa; Suwanda (Bandung Conference Series: Statistics, 2023)
Abstract. Autoregressive model as a classic time series model which is often used in modeling time series data has not been able to explain changes in structure. In addition, other time series models that often deal with structural changes, such as TAR, SETAR, ARCH, and so on, have not been able to overcome the transition opportunities that also often occur in time series data. Thus, the Markov Switching Autoregressive method was introduced which not only addresses structural changes but also pays attention to and explains transition opportunities. This method is applied in modeling inflation rate data in West Java Province, where the inflation rate is an important right to pay attention to because it is related to economic stability and structural changes often occur. Especially in the West Java region as one of the largest provinces in Indonesia. The MS(2)AR(1) model is said to be the best model because it has the smallest BIC value with a BIC value of -91.31212. The MAPE value for the MS(2)AR(1) model is 15% which is said to be good for forecasting. Forecasting is done for the next 12 months. As well as the state duration, it was obtained that the inflation rate remained in an increasing condition for approximately 11 months while it remained in a declining condition for approximately 9 months. Abstrak. Model Autoregressive sebagai model deret waktu klasik yang seringkali digunakan dalam pemodelan data deret waktu belum mampu menjelaskan adanya perubahan struktur. Selain itu, model deret waktu lain yang seringkali mengatasi perubahan struktur seperti TAR, SETAR, ARCH, dan lain sebagainya belum mampu juga mengatasi peluang transisi yang juga seringkali terjadi pada data deret waktu. Dengan demikian, diperkenalkanlah metode Markov Switching Autoregressive yang tidak hanya mengatasi perubahan struktur tapi juga memperhatikan dan menjelaskan adanya peluang transisi. Metode ini diterapkan dalam pemodelan data tingkat Inflasi di Provinsi Jawa Barat, yang dimana tingkat inflasi menjadi suatu hak yang penting untuk diperhatikan karena berkaitan dengan stabilitas perekonomian serta seringkali terjadi perubahan struktur. Terutama di wilayah Jawa Barat sebagai salah satu Provinsi terbesar di Indonesia.Model MS(2)AR(1) dikatakan sebagai model terbaik karena memiliki nilai BIC terkecil dengan nilai BIC sebesar -91,31212. Nilai MAPE untuk model MS(2)AR(1) sebesar 15% yang dikatakan baik untuk peramalan. Peramalan dilakukan untuk 12 bulan kedepan. Serta Durasi state yang diperoleh bahwa tingkat inflasi bertahan dalam kondisi peningkatan kurang lebih 11 bulan sedangkan bertahan pada kondisi penurunan selama kurang lebih 9 bulan.